Analyzing Key Economic Sectors for Sustainable Development in Kuantan Singingi - Ardi Gustri Purbata; Pirmansyah Pirmansyah; Irfan Tanjung; Kasmadi Kasmadi; Syamsul Bahri (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2026)
Regional economic development is a vital aspect in creating community welfare and regional competitiveness. Kuantan Singingi Regency, Riau Province, has significant potential in sectors reliant on natural resources, such as agriculture, forestry, and fisheries. However, these sectors still face challenges in achieving optimal development. The purpose of this study is to identify key sectors in Kuantan Singingi Regency using the Location Quotient (LQ), Shift-Share, and Klassen Typology approaches, and to provide policy recommendations for development based on these leading sectors. The analysis results indicate that agriculture, forestry, and fisheries have a comparative advantage, with an LQ value of 1.80, while other sectors, such as water supply and waste management, also show significant potential. The Shift-Share analysis reveals relatively rapid growth in some sectors, while the Klassen Typology analysis categorizer these sectors based on their contributions to regional GDP and growth rates. These findings provide a foundation for policies that can enhance production capacity, reduce dependence on commodity prices, and strengthen infrastructure to support the sustainable growth of leading sectors. This study is expected to contribute to the formulation of more effective and efficient development policies, which will, in turn, improve the welfare of the people in Kuantan Singingi Regency. Keywords: Regional Development Policy, Location Quotient (LQ), Leading Sectors, Shift-Share, Klassen Typology